Budget expenditures risk management as a priority budget management reform in Ukraine - Stepura, Maryna; Kotina, Hanna (Skhid, 2013)
The article is devoted to the factors that give rise to the risk of budget expenditures, it is justified the necessity of budget risk management, determined the essence of risk management in terms of budget expenditure; outlined the subjects of this process of separation of functions at each stage of the last budget process, set the stages of budget risk management; identified measures to prevent risks to the budget expenditures in Ukraine; analyzed the nature of debt risks that affect the level of funding and public service Ukraine’s debt